Acute Lymphoblastic Leukemia cured without treatment – is That So? - Figueiredo, Carolina; Maia-Moço , Leonardo; Ferreira, Ana Maia; Henrique, Rui; Maia, Iris (Brazilian Journal of Case Reports, 2023)
Spontaneous remission of acute lymphoblastic leukemia is an extremely rare phenomenon. It usually occurs in an aleukemic prodromic setting associated with cytopenias and fever. Nonetheless, this remission status, as far as we know, is always transient, the longest one de-scribed lasting one year. In this case report, we present a 25-months year-old boy with de novo bruises. His complete blood count displayed thrombocytopenia and leukopenia, and biochemistry analysis an increased lactate dehydrogenase. Although bone marrow aspirate was unremarkable, trephine biopsy was suggestive of B-cell acute lymphoblastic leukemia. Within three months, however, he showed a spontaneous clinical and analytical recovery. A repeated biopsy performed two years after was also completely normal. At the time of the writing of this paper, seven years later, the child remains free of progression. It might be the longest spontaneous remission ever described. Opposingly, some histology reports added a differential diagnosis - that the 24.49% immature B-cell infiltrate could, as well, resemble B-hematogones. Hence, we herein try to unveil the mechanism under this particular phenomenon. More efforts should be directed towards research about pre-acute lymphoblastic leukemia and spontaneous remission, so that pediatricians and pathologists can be more comfortable with these rare, but very challenging, situations.